A study on association between personality constructs and entrepreneurial attitudes. (1st January 2012) - Murugesan, R.; Dominic, P.D.D.
Thompson (2004) suggests that entrepreneurship is often a blend of temperament, talent, and technique. Prior research has examined numerous personality constructs in the field of entrepreneurship, but this study focuses on elements of entrepreneurial temperament by examining the relationship between the personality constructs and entrepreneurial attitudes. The primary goal of the current study is to expand upon our understanding of the relationship between personality and entrepreneurial attitudes among college students. The goal is to determine not only if these personality traits are correlated with entrepreneurial attitudes, but also if any gender differences exist. Participants were 456 final year BTech students enrolled at leading technological university at Tiruchirappalli, India. All four of the personality constructs were not found to be significantly correlated with all four of the entrepreneurial attitudes of interest. Strong judgement appears to be the personality construct with the greatest relationship to the entrepreneurial attitudes, as it was related to all four. Our findings insist that differences related to gender alone are not conclusive and that a better understanding of entrepreneurial success requires consideration of the combination of personality traits, attitudes, and outside factors such as economic necessity.